Model Project Based Learning (PJBL) Terdapat Kemampuan Pemahaman Konsep Materi Limas di SMP Muhammadiyah Pagar Alam (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to determine the ability of students' conceptual understanding after the application of the Project Based Learning (PjBL) model on pyramid material in class VII of Muhammadiyah Pagar Alam Middle School in the 2025/2026 Academic Year. The subjects in this study were 30 students using the pre-experimental design method of one group posttest only type. Data collection techniques used in this study include tests and documentation. The data analysis technique is a quantitative descriptive analysis of all collected research data. Starting the stages carried out after learning using the Project Based Learning (PjBL) model, the percentage per indicator of students' conceptual understanding was obtained with the achievement of: indicators restating the concept of 59.12% indicators providing examples and non-examples of 78.33, and problem solving indicators of 83.06%. So it can be concluded that the use of the Project Based Learning (PjBL) model is effective on the conceptual understanding ability of class VII students of Muhammadiyah Pagar Alam Middle School in the 2025/2026 Academic Year with an average percentage reaching 75.91 which is in the good category.